2005
DOI: 10.1073/pnas.0505138102
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin cleavage is triggered by elevated intraocular pressure, and calcineurin inhibition blocks retinal ganglion cell death in experimental glaucoma

Abstract: Increased intraocular pressure (IOP) leads, by an unknown mechanism, to apoptotic retinal ganglion cell (RGC) death in glaucoma. We now report cleavage of the autoinhibitory domain of the protein phosphatase calcineurin (CaN) in two rodent models of increased IOP. Cleaved CaN was not detected in rat or mouse eyes with normal IOP. In in vitro systems, this constitutively active cleaved form of CaN has been reported to lead to apoptosis via dephosphorylation of the proapoptotic Bcl-2 family member, Bad. In a rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 46 publications
5
85
0
2
Order By: Relevance
“…RGC counts in control eyes ranged from 78,000 to 93,600 with a mean (±s.d.) of 84,862 ± 5,753, as previously reported for some eyes (Huang et al, 2005a;Huang et al, 2005b). In eyes with elevated IOP for 10 days RGC counts ranged from 51,100 to 63,029 with a mean of 56,837 ± 4,272, indicating a 33% loss of RGCs (n=8; p < 0.05).…”
Section: Rgc Loss In Experimental Glaucomasupporting
confidence: 76%
See 1 more Smart Citation
“…RGC counts in control eyes ranged from 78,000 to 93,600 with a mean (±s.d.) of 84,862 ± 5,753, as previously reported for some eyes (Huang et al, 2005a;Huang et al, 2005b). In eyes with elevated IOP for 10 days RGC counts ranged from 51,100 to 63,029 with a mean of 56,837 ± 4,272, indicating a 33% loss of RGCs (n=8; p < 0.05).…”
Section: Rgc Loss In Experimental Glaucomasupporting
confidence: 76%
“…We also applied the method of cross-sectional stereological counting as a tool for assessing RGC survival and neuroprotection in experimental glaucoma as a result of drug treatment. In glaucoma eyes treated with the calcineurin inhibitor FK506, stereological counting methods detected a 50% protection of RGCs (Huang et al, 2005b).…”
Section: Discussionmentioning
confidence: 96%
“…Inhibiting calcineurin activation reduces BAD dephosphorylation and improves cell survival (Wang et al, 1999a;Springer et al, 2000;Uchino et al, 2002;Berthier et al, 2004;Mano et al, 2004;Shou et al, 2004;Watabe and Nakaki, 2004;Yang et al, 2004a;Biswas et al, 2005;Cardoso and Oliveira, 2005;Huang et al, 2005). Reducing calcineurin activation also reduces the downstream caspase activity (Springer et al, 2000;Nottingham et al, 2002;Agostinho and Oliveira, 2003;Cardoso and Oliveira, 2005;Grosskreutz et al, 2005).…”
Section: Bcl-2 Anti-apoptotic Proteinsmentioning
confidence: 99%
“…Once Bad is on the outer mitochondrial members, it will bind to anti-apoptotic Bcl-2 or Bcl-XL and promote release of cytochrome c. (Wang et al, 1999;Heckman et al, 2006) Calcineurin activation and cytochrome c release has been linked with RGC death after optic nerve crush. (Huang et al, 2005) Lastly, RGC death has been shown to be attenuated in experimental models of optic nerve crush after treatment with a calcineurin inhibitor, FK506 (Huang et al, 2005). Calpain is a Ca 2+ -dependent cysteine protease that is implicated in many neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease and Huntington's disease (Nixon, 2003;Goll et al, 2003) Calpain activates calcineurin and transforms it into its constitutively activated form.…”
mentioning
confidence: 99%